The (In)visible life of Juan Filloy: Revising the Myth of the Occult Writer - de Olmos, Candelaria (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Throughout his artist career, the writer Juan Filloy (Córdoba, 1894-2000) was subject of extensive interviews, and along with that, one must include the critical notes in diverse social media. Within the biography and the autobiography, these texts have built an image around the writer who voluntarily went ignored but unfairly forgotten. A close look through this corpus permits one to see that this built image revolves around two main axes: his residence in a province town and the edition of his books privately. Moreover, within this context, one can also see consistency and transformation. According to my hypothesis, the plot of these texts revolves around two essential themes: the first one looks at the image of the cult writer, and the second one, consecutively unearth the hidden writer. Furthermore, a close view to his personal correspondence invites to question this writing and to create another one that could correspond to the rationale that made this one become visible.